Roccipi's Analysis of the Policy on the Implementation of Professional Zakat for Civil Servants in Sinjai Regency - Andi Muh. Taqiyuddin BN; Muh. Sadli Sabir; Ahmad Arief; Budiarti A Rahman; Abdul Syatar (JOSH: Journal of Sharia, 2025)
This study aims to examine Roccipi's analysis of the implementation of professional zakat policy for civil servants in Sinjai Regency. This is a qualitative study. The research design is field research. The results of this study indicate that based on the analysis using the Roccipi method, there is an opportunity to accelerate the implementation of professional zakat for civil servants in Sinjai Regency in the form of the large potential for professional zakat in Sinjai Regency. Additionally, challenges were identified that hinder the implementation of professional zakat for civil servants in Sinjai Regency, including the absence of local regulations specifically governing the implementation of professional zakat for civil servants in Sinjai Regency, an incomplete integration of the muzakki database, low transparency and digitalisation, insufficient socialisation, the absence of performance evaluations for UPZ in relevant agencies, limited understanding among muzakki, differences in perspectives regarding the obligation of professional zakat, insufficient competence of zakat collectors, limited support from the local government and the Ministry of Religion, poor communication among zakat collectors, the insignificant contribution of professional zakat to the local budget, and some civil servants believe that zakat is merely an individual responsibility.